Comportamento de vigas protendidas pré-moldadas com ligações semi-rígidas - Catoia, Bruna (2007)
The behaviour of prestressed precast beams is directly affected by the rotational stiffness of the end connections. Although the prestressed beam presents a linear behaviour in service, the effective behaviour of the precast beam depends on the interaction of the beam with the behaviour of its connections. The majority of the experimental investigations on semi-rigid connections in precast concrete structures are focused on the testing of isolated models of connections aiming to the characterization of their moment-rotation relationships. However, the effective behaviour of precast beams with semi-rigid connections can only be determined through tests of precast subframes, wherein the interaction of the beam with its connections can be evaluated. The present research presents a development of an experimental procedure for testing of precast subframes with semi-rigid connections, which integrates analytical equations, allowing estimate the partial restrained moment at the beam-column connections. Using this approach, this research presents the results of an experimental investigation. With the experimental inquiry of the prestressed beam behavior together with the beam-column connections of extremity, through physical tests, was possible esteem the partial restrained in the beam-column connections, despite in exploratory character. Were testing two models, being one compose for a prestressed beam with semi-rigid connections, and the other compose for a simply supported prestressed beam With the analyses of the experimental results for the studied models, the effective restrained of the connections, in other words, the capacity of restriction to the rotation of beam-column connections of extremity in the U.L.S, was esteem as being a value between 60% and 70%, presenting, thus, a good performance. Although these results are restricted to the negative moments, it gives credit that these connections possess one high potential for application in porches, because the detail used in the interface between the beam and the column made possible a bigger capacity of restriction to the rotation of the connection